ChemInform Abstract: Pd(II) Trifluoroacetate Complexes Containing Chelating Phosphine Ligands: Synthesis, Structures, and Catalysis. Issue 21 (6th May 2016) - Kim, Kun‐Woo; Kim, Yong‐Joo; Lim, Hye Jin; Lee, Soon W.
Abstract: Biaryls are prepared by Suzuki—Miyaura coupling of aryl bromides and aryl boronic acids using the title palladium complex as highly active catalyst.